Islamic Deviationist Movements (IDMs): An analytical inquiry into Southeast Asia - Yousif, Ahmad (2011)
While classical Muslim scholars such as al-Shahrastani, al-Kalbi, al-Baghdadi, Ibn Hazim, Ibn al-Jawzi and others undertook numerous studies and made significant contributions to the field of “Religious Sects and Divisions” (al-Milal wa al-Nihal), the majority of academic institutions in the Muslim world today have given scant attention to new religious trends, sects, and divisions within Islam. Nevertheless, there have been some Muslim scholars in the 20th century such as Abu Zuhra of Egypt, Irfan Abdul Hamid of Iraq, Abu al-Hasan al-Nadawi of India, and Mahmud Saedon Othman of Brunei, who have made notable contributions to the field. Frequently, contemporary Muslim thinkers have tended to employ the term “Islamic Deviationist Movements (IDMs) or Ajaran Sesat (in Malay) to denote any group that has strayed from the mainstream of Islam. By way of contrast, Western scholars have often preferred to use the more constructive term “New Religious Movements” (NRMs) to designate any new, “breakaway” religious group from a traditional religion. While Muslim writers have approached the subject from a historical or socio-religious perspective, few have utilized a scientific methodology based on fieldwork experience in order to study Islamic “deviationist” movements; particularly those of mystical orientation. This paper will examine the controversy over defining the term “deviation group.” We briefly compare Western and Islamic methodologies for studying IDMs, and then assess the impact of IDMs on Muslim society. Finally, and in light of the contemporary situation in Southeast Asia, a number of recommendations will be made on how Muslim scholars can effectively study and better understand Islamic “deviation” movements within the purview of a scientific framework.